Antimicrobial Potential of Carvacrol against Uropathogenic Escherichia coli via Membrane Disruption, Depolarization, and Reactive Oxygen Species Generation - Khan, Imran; Bahuguna, Ashutosh; Kumar, Pradeep; Bajpai, Vivek K.; Kang, Sun C. (Frontiers in Microbiology, 2017)
Bacterial resistance to antibiotics poses a serious threat to cure diseases associated with microbial infection. Among the resistant bacteria, extended-spectrum β-lactamase (ESBL)-producing bacteria are the most concerned one as they encode the enzyme β-lactamase that confers resistance to most β-lactam antibiotics. The present study was carried out to determine the antimicrobial potential and the principle mechanism of action of carvacrol against ESBL Escherichia coli isolated from ascitic fluid of a patient having a urinary tract infection (UTI). Carvacrol exhibited a minimum inhibitory concentration (MIC) of 450 μg/ml at which it reduced E. coli cell counts significantly in a time-dependent manner. Carvacrol completely diminished the growth of E. coli after 2 h of incubation at its MIC. Fluorescent imaging displayed the elevated reactive oxygen species (ROS) level and bacterial membrane depolarization leading to E. coli cell death in presence of carvacrol at its MIC. Furthermore, carvacrol displayed a severe detrimental effect on bacterial membrane disruption and cellular material release. In addition, a significant effect of carvacrol at sub-inhibitory concentration was observed on motility of E. coli cells and invasion of human colon HCT-116 cells in an ex vivo model. Based on the results, we conclude a potential antimicrobial role of carvacrol against ESBL E. coli.